Karakteristik Medan Listrik-Dekat Petir Positive Cloud to Ground - Seftiani, Yudia Meka; Hazmi, Ariadi; Novizon, Novizon; Abadi, Akbar; Widia, Riza (Elektron : Jurnal Ilmiah, 2023)
This study was conducted on 19 electric field data near positive lightning cloud to ground (+CG). The electric field change of +CG lightning consist of preliminary breakdown (PB) and return stroke (RS). The analysis conducted in this research are: PB/RS ratio, PB-RS separation, pre-return stroke duration, pulse train duration, and individual pulse duration. Furthermore, the relationship between +CG lightning and cloud image satellite was observed the average value of PB/RS ratio, PB-RS separation, prereturn stroke duration, pulse train duration and individual pulse duration were 13,89%, 91,53 ms, 102,23 ms, 1,20 ms,150,31 μs, respectively.